Limitations to Access to Justice in Human Rights-Based Climate Change Litigation before the CJEU and the ECtHR - Pohjankukka, Reetta (My University, 2023)
While the dangerous effects of climate change keep on appearing more and more, the internationally recognized human rights to a healthy climate or healthy environment are absent. In the absence of explicit legislation protecting such human rights, the people have turned to seek justice through the courts, however ending up facing multiple barriers for their access to justice within its meaning in this study. The issue of climate change is by its very nature unique in the traditional legal framework especially due to its future-oriented perspective and challenges related to protecting the rights of future generations. This study systematically presents the relevant international legislation and the related jurisprudence in order to draw a conclusion on the limitations related to the availability of access to justice in human rights-based climate change litigation within the reach of the CJEU and the ECtHR. Thus, the aim of this study is to clarify the current legal position of the matter within the defined parameters through legal dogmatics and critical analysis of the judicial practice. The limitations recognized in this study include restricting substantive and procedural access to justice provisions, strict admissibility criteria of the CJEU and the ECtHR and challenges related to establishing judicially enforceable basis for these human rights claims, attributing the state's emissions to climate change overall, linking climate change to a particular climate change effect, dividing the responsibilities between possible multiple wrongdoers, and matters of causality and temporality.

Ihmisoikeuksia terveelliseen ilmastoon tai terveelliseen ympäristöön ei ole kansainvälisesti tunnistettu ilmastonmuutoksen vaarallisten seurausten jatkuvasta lisääntymisestä huolimatta. Näitä oikeuksia eksplisiittisesti suojaavien ihmisoikeussäännösten puuttuessa ihmiset ovat kääntyneet tuomioistuinten puoleen, kuitenkin päätyen kohtaamaan useita rajoituksia oikeuden saatavuuteen, tutkimuksessa määritellyn mukaisesti. Ilmastonmuutos on perimmäiseltä luonteeltaan perinteisen lainsäädäntökehyksen näkökulmasta uniikki johtuen sen tulevaisuuteen orientoituneesta perspektiivistä sekä tulevien sukupolvien oikeuksien suojelemiseen liittyvistä haasteista. Tavoitteenaan vetää johtopäätös oikeuden saatavuuteen liittyvistä rajoitteista ihmisoikeusperusteisissa ilmasto-oikeuskanteissa Euroopan unionin tuomioistuimen sekä Euroopan ihmisoikeustuomioistuinten toimivallan alla, tämä tutkimus käy systemaattisesti läpi relevantin kansainvälisen sääntelyn sekä siihen liittyvän oikeuskäytännön. Siispä, tutkimuksen tarkoitus on selventää asian tämän hetkistä oikeustilaa määriteltyjen viitekehysten sisällä teoreettisen lainopin sekä kriittisen analyysin metodein. Tutkimuksessa tunnistetaan rajoituksia liittyen substantiiviseen sekä prosessuaaliseen oikeuden saatavuuteen, kyseisten tuomioistuinten tiukkoihin hakemuksen tutkittavaksi ottamista koskeviin vaatimuksiin, oikeudellisesti täytäntöönpanokelpoisen ihmisoikeusperustan löytämiseen, valtion päästöjen yhdistämiseen ilmastonmuutokseen, vastuun jakamiseen usean mahdollisen väärintekijän kesken sekä kausaliteettiin ja aikaan liittyviin haasteisiin.
Keywords: climate law, environmental law, international law, access to justice, judicial practice